Analysis of the Role of Age Factors on Hemoglobin, Leukocyte and Platelet Levels in Breast Cancer Patients Post Chemotherapy 3 Cycles at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Rahmaniar, Suci; Benny Kusuma; Irfanuddin (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2024)
Introduction: Breast cancer is one of the most common cancers in women. Chemotherapy is one of the main modalities in the treatment of breast cancer, but it can cause hematological side effects such as anemia, leukopenia, and thrombocytopenia. Age is one factor that is thought to influence these side effects. Methods: This study used an analytical observational design with data collected from medical records of breast cancer patients who had undergone 3 cycles of chemotherapy at Dr. Mohammad Hoesin General Hospital Palembang. Data on hemoglobin, leukocyte, and platelet levels before and after chemotherapy were analyzed using the t-test and ANOVA. Results: A significant decrease in hemoglobin levels was observed in patients aged > 60 years after chemotherapy (p < 0.05). Leukocyte levels showed fluctuations, especially in patients aged <40 years, while platelet levels fluctuated more in patients aged <40 years and decreased in the age group 40-60 years after chemotherapy. Conclusion: Age does not significantly influence the decrease in hemoglobin, leukocyte, and platelet levels in breast cancer patients after chemotherapy.